P439 Monitoring inflammatory Bowel disease activity in a virtual biologic clinic: The effects of proactive therapeutic drug monitoring on patient reported outcome measures. (16th January 2018) - Mc Gettigan, N; McNally, M; Deane, C; Keogh, A; Costello, R; Slattery, E
Abstract: Background: Proactive therapeutic drug monitoring (P-TDM) to optimise maintenance Infliximab (IFX) levels prior to loss of response reduces risk of treatment failure, IBD-related surgery and hospitalisation when compared with reactive monitoring (R-TDM). The aim of this study was to investigate if P-TDM in a virtual biologic clinic (VBC) improves patient disease control as determined by patient reported outcome measures (PROMs) and to evaluate biomarkers of disease activity. Methods: Retrospective observational study with crossover design. Data were collected from commencement of VBC in June 2016 to September 2017. All IBD patients on IFX in the VBC were included. PROMs were recorded using the IBD-Questionnaire and Visual Analogue Scale (VAS). Results: One hundred and twenty-three patients were included in the study – 51% were male ( n = 63), 66% had Crohn's disease ( n = 81). 78% ( n = 96) were receiving IFX prior to June 2016. IBD VAS scores improved from a median score of 80 of 100 with reactive monitoring (95% CI: 80, 85) to a median of 90 of 100 at 1 year with P-TDM (95% CI: 85, 90). No change was observed in the median score for IBD-Control (13/16) when patients switched from R-TDM to P-TDM (95% CI: 12, 14). Faecal calprotectin levels decreased from a median score of 109 (95% CI: 56.5, 167.6) with R-TDM to a median score of 41 (95% CI: 22, 55) with P-TDM. The median CRP for R-TDM was 2.3 (95% CI: 1.6, 3.1) with a range of 0.6–295, compared with a median value of 1.8 (95% CI: 1.4, 2.5) with a range of 0.6–43 for P-TDM. Twenty-five patients (20%) were dose escalated and 15 patients (12%) were dose de-escalated (Figure 2). At 1 year, the median IBD-VAS score was 90 of 100 (95% CI: 84.3, 90) in dose-escalated patients and 82.5 of 100 (95% CI: 75, 93.6) in de-escalated patients. There were 19 admissions in the R-TDM group. Seventeen of 19 (89%) were due IBD flares. The P-TDM group had 12 admissions. Six of 12 (50%) due to IBD flares. Five VBC patients (4%) proceeded to surgery. Only one serious infusion reaction was reported. Conclusions: There was a modest improvement in PROMs overall. The majority of patients with dose adjustments showed improvement in their median VAS score. The introduction of P-TDM resulted in a significant reduction in hospital admissions, in particular the number of crisis admissions for IBD flares.